Hardware development of electrical capacitance tomography for imaging a mixture of water and oil - Ruzairi Abdul Rahim, author; Fazlul Rahman Mohd. Yunus, author; The Second International Conference on control, Instrumentation and Mechatronic Engineering (CIM09) (2009 : Melacca) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL